Highly boron-selective adsorbent by radiation induced grafting of N-vinylformamide on polyethylene/polypropylene sheet followed by hydrolysis and glycidol treatment - Afolabi, H.K. (Elsevier Ltd, 2021)
An adsorbent containing glycidolized poly(vinylamine) ligand with a remarkably high boron selectivity was prepared by modification of fibrous polyethylene/polypropylene (PE/PP) nonwoven sheet by radiation induced grafting (RIG) of N-vinylformamide (NVF) followed by hydrolysis and subsequent functionalization with glycidol. The variation of the absorbed dose and monomer concentration was used to control the content of the grafted P(NVF). Fourier transform infrared (FTIR), X-ray photoelectron spectroscopy (XPS) and scanning electron microscope (SEM) were used to verify the chemical and morphological changes accompanied the applied procedure and boron loading. The fibrous adsorbent with fully hydrolyzed P(NVF) grafts of 120 exhibited a superior boron adsorption capacity of 21.4 mg/g compared to commercial and researched counterparts at pH 7. Â© 2021 Elsevier Ltd